PEMBUATAN LEMBAR KERJA PESERTA DIDIK (LKPD) MULTIMEDIA INTERAKTIF MENGGUNAKAN COURSE LAB BERBASIS PENDEKATAN SAINTIFIK PADA PEMBELAJARAN FISIKA KELAS X SMA/MA - Lara Cesilia Elwi; Festiyed Festiyed; Djusmaini Djusmaini (Universitas Negeri Padang, 2017)
Media learning used by educator on now could not make learners motivated and active in learning physics. In addition, still a lot of her school who has not use worksheets learners (LKPD) appropriate for the curriculum 2013 by stressing the rendering approach. LKS used at the school limited of print and not yet interactive can make students encounter of a lab work. The completion of this problem made interactive LKPD multimedia used as a guide lab work. LKPD multimedia use lab interactive course with approach based rendering used in learning physics class x with matter a circular irregular. Research conducted including research development (research and development). In the study is done just got two stages, test validity and the praktikalitas. To feasibility study in LKPD this undergone a validity by the energy and expert who is lecturers physics teachers undergone a try limited. Objects on this research LKPD multimedia interactive. The subject of study is 3 people validator, 2 practitioner by teachers, and 14 practitioner by students. Based on the research was done on interactive LKPD multimedia there are two results. The first validation are the very valid with average 91,6%. Both results of praktikalitas by teachers are the very practical average value of 91,1%. While the praktikalitas by students are in the practical having value of 82,3%